When happiness strengthens engagement and performance: the role of happiness at work as a resource for experienced employees and newcomers - Fröhlich, Patrik; Radaca, Elvira; Diestel, Stefan (Frontiers in Psychology, 2025)
This research investigates the interactive effects of happiness at work and interest taking on work engagement and extra-productive behaviors across experienced employees and newcomers.ObjectiveThe article investigates how happiness at work can serve as a key resource in enhancing work engagement and extra-productive behaviors such as adaptive performance and organizational citizenship behavior (OCB) in newcomers and experienced employees. Furthermore, it clarifies the interactive effects of the personal resource interest-taking in enhancing the effectiveness of happiness at work, particularly by examining how interest-taking moderates the relationship between happiness at work and work engagement.MethodsWe conducted two longitudinal studies among newcomers (N = 126) and experienced employees (N = 126) of various industries. For data analysis, we applied multilevel modeling to account for the nested structure of the data. We conducted 2-1-1 moderated mediation analyses to test indirect and conditional effects along the a-path of the proposed model.ResultsAcross both studies, our findings indicate indirect effects of happiness at work on extra-productive behavior via work engagement. Interest-taking strengthens the impact of happiness at work on work engagement for newcomers but not for experienced employees. These new insights into the relationship between happiness at work, work engagement, and extra-productive behavior can aid organizations in enhancing the performance and motivation of employees.ConclusionOur findings demonstrate that happiness at work indirectly promotes OCB and adaptive performance through increased work engagement for all employees, regardless of their tenure. The moderating role of interest-taking is especially relevant for newcomers, suggesting that organizations can boost positive outcomes by fostering happiness at work in early tenure.